Biofilm Application as Biomonitoring Agent in Heavy Metals Pb2+ and Cr6+ in Ngimboh Coastal, Ujungpangkah, Gresik - Agung Riswandi; Muhammad Mahmudi; Andi Kurniawan; Lutfi Nimatus Salamah (Journal of Wetlands Environmental Management, 2019)
Biomonitoring is the use of organisms to monitor and assess/detect the condition of an environment. Ngimboh Coast is a coastal line in Ujungpangkah Subdistrict, East Java (Indonesia) which functions as a vessel berth, TPI, and shipyard industry which has the potential to dispose of waste containing Pb2+ and Cr6+ which affect the physical condition of chemicals and organisms in these waters. This study aims to determine the Biofilm can be a biomonitoring agent in heavy metals Pb2+ and Cr6+ and to know the physical chemical conditions in the Ngimboh coast, Ujungpangkah District, Gresik. This study uses a survey method. Biofilm, sediment and water sampling was carried out at 3 sampling points, namely the first sampling point area close to the disposal of shipyard industrial waste, the second sampling point was an empty land area, and sampling point three was the estuary area. The parameters were measured such as physical properties (temperature, current speed, water depth), chemical properties (pH, DO, salinity), metal content of Pb2+ and Cr6+ on biofilms, sediments and water.